Syndication and Robust Collusion in Financial Markets - Vinicius Carrasco; Gustavo Manso (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2006)
This paper investigates the extent to which syndication in financial markets is related to collusive behavior. A group of financiers who have private information regarding their capability of monitoring an entrepreneur must decide whether to provide a loan individually in a competitive fashion, or provide it collectively. When deciding whether to provide the loan collectively, the lenders bargain over their participation, on who will be monitoring the lender (the leader), and on pricing. It is shown that if the bargaining stage is robust to timing of communication of their private information (Ex-Post Incentive Compatibility), and if the lenders believe it is better to agree on a collective deal than competing, positive participation in the loan is given to all lenders even when side payments are allowed. Hence, we show that syndication is the optimal response of colluding lenders to the communication costs resulting from the negotiations between them for a given loan. Syndication improves on pricing but introduces a distortion by leaving the most effective monitor with less than full participation in the loan. Necessary conditions for syndication prevailing over competition are provided.
Keywords: 330; Finanzmarkt; Kartell; Unternehmensfinanzierung; Theorie